Ectopic expression of the cation-chloride cotransporter KCC2 in blood exosomes as a biomarker for functional rehabilitation - Caccialupi Da Prato, L.; Rezzag Lebza, A.; Consumi, A.; Tessier, M.; Srinivasan, A.; Rivera, C.; Laurin, J.; Pellegrino, C. (Frontiers in Molecular Neuroscience, 2025)
BackgroundTraumatic brain injury (TBI) is a major cause of disabilities in industrialized countries. Cognitive decline typically occurs in the chronic phase of the condition, following cellular and molecular processes. In this study, we described the use of KCC2, a neuronal-specific potassium–chloride cotransporter, as a potent biomarker to predict cognitive dysfunction after TBI.MethodsUsing neuronal and total exosome collections from the blood serum of the controls and patients with TBI, we were able to anticipate the decline in cognitive performance.ResultsAfter TBI, we observed a significant and persistent loss of KCC2 expression in the blood exosomes, which was correlated with the changes in the network activity and cellular processes such as secondary neurogenesis. Furthermore, we established a correlation between this decrease in KCC2 expression and the long-term consequences of brain trauma and identified a link between the loss of KCC2 expression and the emergence of depressive-like behavior observed in the mice.ConclusionWe successfully validated our previous findings, supporting the potential therapeutic benefits of bumetanide in mitigating post-traumatic depression (PTD) following TBI. This effect was correlated with the recovery of KCC2 expression in the blood exosomes, the prevention of extensive neuronal loss among the interneurons, and changes in secondary neurogenesis.